Is God a delusion?: a reply to religion's cultured despisers - Reitan, Eric (Wiley-Blackwell, 2009)
On religion and equivocation -- "The God hypothesis" and the concept of God -- Divine tyranny and the goodness of God -- Science, transcendence, and meaning -- Philosophy and God's existence, part I -- Philosophy and God's existence, part II -- Religious consciousness -- The substance of things hoped for -- Evil and the meaning of life -- The root of all evil?